2016
DOI: 10.1002/mrd.22616
|View full text |Cite
|
Sign up to set email alerts
|

Position-dependent interactions of Y-box protein 2 (YBX2) with mRNA enable mRNA storage in round spermatids by repressing mRNA translation and blocking translation-dependent mRNA decay

Abstract: SUMMARYMany mRNAs encoding proteins needed for the construction of the specialized organelles of spermatozoa are stored as translationally repressed, free messenger ribonucleoproteins in round spermatids, to be actively translated in elongating and elongated spermatids. The factors that repress translation in round spermatids, however, have been elusive. Two lines of evidence implicate the highly abundant and well-known translational repressor, Y-box protein 2 (YBX2), as a critical factor: First, protamine 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 113 publications
(278 reference statements)
0
7
0
Order By: Relevance
“…The ZMYND15 gene is primordial for sperm production and male fertility [66]. The YBX2 gene codifies a protein required for mammal development and fertility because knockout mice for this gene presented disruption of spermatogenesis and oogenesis [6769]. The TMEM95 gene codifies a protein located at the surface of spermatozoa and deficiency of TMEM95 severely compromises male reproductive performance, resulting in subfertility in cattle [70].…”
Section: Discussionmentioning
confidence: 99%
“…The ZMYND15 gene is primordial for sperm production and male fertility [66]. The YBX2 gene codifies a protein required for mammal development and fertility because knockout mice for this gene presented disruption of spermatogenesis and oogenesis [6769]. The TMEM95 gene codifies a protein located at the surface of spermatozoa and deficiency of TMEM95 severely compromises male reproductive performance, resulting in subfertility in cattle [70].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the transcripts, such as Tmco5, which are translated after elongating spermatids for spermiogenesis, are transcribed in the round spermatids and are stored as translationally repressed state until use. With regards to this regulatory mechanism, RNA-binding proteins and corresponding cis-elements, mainly located in the 3' untranslated region, are known to be involved [32]. For example, the mRNA for Protamin 2 is transcribed at step 7.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested that YBX1 and YBX2 are key players in modulating BAT adipogenesis and thermogenesis by affecting RNA stability. Regarding one of the well-characterized functions of YBXs is regulating translation [ 91 , 92 ], and whether these proteins are involved in the translation of target RNA is not yet answered. In addition, the role of Ybx3 in BAT is little known.…”
Section: Regulation Of Adipogenesis and Adipose Function By Rbpsmentioning
confidence: 99%